Resultados monetarios de la Sustentabilidad presentados en Cuatro Cuentas de Resultados: Una propuesta para las Pymes en México (2021)
The eminent deterioration of the planet sets the challenge for human beings to contribute to minimize it. One way to contribute by some public accountants is to engage with the needs of monetary records, related to social and environmental aspects to demonstrate the activity of companies in favor of sustainability. So the purpose of this paper is to investigate about sustainable accounting and how Mexican small and medium-sized enterprises (SMEs) can present the monetary results of sustainable actions, with the proposed use of four income statements (CCR, in Spanish), based on the analysis and comparison of Elkington's Triple Bottom Line (TBL) matrix (1998). With a descriptive and exploratory study, results were obtained that show the benefit for SMEs when displaying their work in favor of sustainability, with the proposal of the CCR matrix.